FAKTOR – FAKTOR YANG MENYEBABKAN SUATU PERUSAHAAN MELAKUKAN TAX AVOIDANCE - Berliana Putri Kurniadi; Yuniarwati Yuniarwati (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
The purpose of this study is to analyze the effects of profitability, leverage, liquidity, and firm size on tax avoidance of industrial companies listed on the Indonesia Stock Exchange (IDX). The population for this study is from the period 2019 – 2021 using 87 data which consists of 29 industrial companies. The data analysis method used in this study is multiple linear regression analysis to test the hypothesis, SPSS Version 22 Software program and Microsoft Excel 2013 to process data from this research. The results of this study indicate that profitability (ROE) has a significant and negative effect on tax avoidance. While leverage (DER), liquidity (CR) and firm size (SIZE) does not have a significant and positive effect on tax avoidance.